OPTIMASI PADA PENAMBAHAN ZAT ADITIF TERHADAP NILAI KALOR BRIKET CANGKANG KELAPA SAWIT - Bahrin Bahrin; Desi Ardilla; Muhammad Taufik (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
Abstract The porpuse of research was to knew influence and the heat of combustion palm oil briquette with added additive substance. The work principle of research included foreword working was preparations raw material (Oil palm eggshell) and additive substance (rice husk, bagasse, shell of coconut).Raw materials of palm oil was burning in the vurnace at temperature 400 0C for four o’clock and refined at the measure of 1 mm and so also above additive substance was refined at the measure of 1.6 mm, 1 mm, and 0.71 mm but non burning. Oil palm eggshell powder and additive substance was blended then added amylum as much as 30 % from Oil palm eggshell weight. The compound was taken into press hydrolik to formed and then drying at temperature 120 0C for 90 minute. The briquet that produced was characterized with heat of combustion, water-content, and ash-content-ash. The result of research was palm oil briquette with added rice husk produced heat of combustion of 7.322.49 kal/gr, content-water 15.14 %, content ash 7.0 %, the bagasse heat of combustion of 10.837.29 kal/gr, content-water 15.26 %, content-ash 18.75 %, and the shell of coconut heat of combustion of 9.079.89 kal/gr, content-water 3.25 %, content-ash 8,09 %. The optimum product of this research was palm oil briquette with added the shell of coconut for 15 gr with measure of 1 mm got heat of combustion of 9.079,89 kal/gr, content-water 3.25 %, content-ash 8.00 %.Keyword: briquette, Oil palm eggshell, additive substance